Measuring the Welfare Effects of Slum Improvement Programs: The Case of Mumbai - Takeuchi, Akie (2012)
This paper evaluates the welfare effects of in situ slum upgrading and relocation programs using data for 5000 households in Mumbai, India. We estimate a model of residential location choice in which households value the ethnic composition of neighborhoods and employment accessibility in addition to housing characteristics. The importance of neighborhood composition and employment access implies that relocation programs must be designed carefully if they are to be welfare-enhancing. The value of our model is that it allows us to determine the magnitude of these effects. It also allows us to determine the value households place on in situ improvements, which policymakers need to know if they are to design housing programs that permit cost recovery.